Penerapan Pendekatan PDIA dalam Meningkatkan Efektivitas PKL pada Konsentrasi Keahlian TKJ di SMK: Sebuah Kajian Teoretis - Indra Nova Saputra; Luthfiyah Nurlaela; Rommy Mochamad Ramdhani; Theodorus Wiyanto Wibowo; I Gusti Putu Asto Buditjahjanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Practical Work Placement (Praktik Kerja Lapangan/PKL) is positioned as a core subject in the Merdeka Curriculum and plays a strategic role in vocational education, particularly for students in the Computer and Network Engineering (TKJ) specialization at vocational high schools. Through PKL, students are expected to internalize work culture, strengthen technical competencies, and gain an authentic understanding of real workplace practices. Nevertheless, various studies indicate that the implementation of PKL often faces persistent challenges, such as mismatches between students’ competencies and workplace assignments, inconsistent mentoring quality, and limited evaluation mechanisms, which may hinder the achievement of learning outcomes. This article presents a theoretical review that explores the potential application of the Problem Driven Iterative Adaptation (PDIA) approach as a managerial framework to enhance the effectiveness of PKL. A literature review method was employed to examine policy documents, curriculum guidelines, and academic studies related to PKL, vocational education management, and adaptive change approaches over the last decade. This method was selected to allow a comprehensive synthesis of concepts and practices without relying on field data, focusing instead on understanding structural and managerial issues in PKL implementation. The analysis suggests that PDIA offers a flexible and context-sensitive framework for identifying root problems, implementing incremental improvements, and fostering continuous learning through collaboration between schools and industry partners. Overall, this study highlights that PDIA can support more adaptive PKL management and contribute to improving the relevance and quality of vocational learning experiences for TKJ students.